A large-scale borehole heat store during five years of operation - Nordell, Bo (Luleå tekniska universitet, Arkitektur och vatten, 1988)
The borehole heat store in Luleå, Sweden, was built in 1982/83. The store consists of 115, 000 m3 of chrystalline rock. The rock volume is perforated by 120 boreholes to a depth of 65 m of which 3.5 m penetrate the soil. The total active borehole length is 7380 m. The rock temperature varies between 30 to 60 °c during the year. During six month of the summer season 2.0 GWh is charged of wich 50% is recovered during the winter season. The extracted heat is utilized for space heating of one of the university buildings. The research project includes evaluation of the construction work and five years of operation. The measurement programme was completed in May 1988. A final report will be published in the autumn of 1988. The storage system is now in its 6th charging period. This paper gives a brief description of the plant. Experiences from the operation period and operation data of the plant are given. ISBN för värdpublikation: 9061918278